Mesoporous Organic-Inorganic Non-Siliceous Hybrid Materials: Basic Principles and Promising Multifunctionality - Zhu, Yun-Pei (Springer, 2015)
This book provides extensive information on organic-inorganic hybrid materials with controllable compositions and structures developed over the past few decades, including metal sulfonates, carboxylates, phosphonates, metal-organic frameworks (MOFs), etc. A variety of judicious strategies for optimizing mesoporosity are also introduced, aiming at realizing the corresponding superiorities of hybrid frameworks in practical applications at the nano-/meso-scale. The morphological design and modification methods are also described in detail, which extend the potential application range of hybrid materials from traditional areas to high-tech fields.